2018
DOI: 10.12669/pjms.343.14722
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section rate amongst Obstetricians at a tertiary-care hospital of Karachi

Abstract: Objective:To analyze the Caesarean Section (CS) rate among different groups of consultants dealing with Nulliparous Term Singleton pregnancy with Vertex (NTSV) presentation delivering at a tertiary care hospital of Karachi over four months.Methods:This is a secondary analysis of a retrospective data that analyzed factors affecting the CS-rate of NTSV patients. Patients with CS (n=106) were taken as cases and vaginal deliveries (n=106) as controls. This was an unmatched retrospective case-control study.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…14 Ahmed I et al noted the effect of counselling on the rates of cesarean section. 15 They observed that the rates of the cesarean section were more among women who were not given counselling during pregnancy and who were not attended by full time faculty. But the differences were not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Ahmed I et al noted the effect of counselling on the rates of cesarean section. 15 They observed that the rates of the cesarean section were more among women who were not given counselling during pregnancy and who were not attended by full time faculty. But the differences were not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…They recommended more studies especially with large sample size and multiple centre studies and prospective studies. 15…”
Section: Discussionmentioning
confidence: 99%